Design flow factors using socioeconomic based synthetic wastewater hydrographs for small communities - Elnakar, Haitham Yousri (AUC Knowledge Fountain, 2013)
Reliable estimation of sewage flow rates is essential for the proper design of sewers, pumping stations, and treatment plants. The widely used design peaking factors for sewerage systems are usually related to the population served or the average sewage flow rate ignoring the difference between communities having same population but different socio-economic conditions and water use practice. In this study, a simulation model is developed to generate synthetic wastewater flow hydrographs resulting from a community with specific socio-economic conditions. The synthetic hydrographs are developed while retaining their commonly observed random behavior. The socioeconomic characteristics of a community are accounted for by the composition of the community and its social categories, the water use pattern of every category during the various daily activities (weekday and weekend), and the water use facilities (fixtures and appliances) available to the community. The model utilizes different water use patterns by every social group for every appliance during the different day types e.g. weekday and weekend. The use patterns account for the stochastic nature of use in terms of number of uses, duration of use and times of use in the day. Randomly generated hydrographs are generated for weekdays and weekends. The daily sewer hydrographs are transformed by hydraulic routing through the sump --pump to daily pumped flow hydrographs conveying wastewater to the treatment plant. One year of generated record of both hydrographs is statistically analyzed to derive two sets of flow factor curves to be used for the design of sewers, and the various components of the treatment plant. The flow factors are given in terms of the duration when the flow factor is sustained and the probability that the flow is not- . The proposed model was applied to a small community with certain socio-economic conditions and population and the resulting design peaking factors were obtained and compared to flow factors derived from a limited measurement program of the wastewater hydrographs generated by the community. The results indicate the usefulness of the proposed model in predicting probable flow hydrographs from selected communities with specific socio-economic setting and population. A parametric study is carried out to investigate the effect of the community population, class and socio-economic conditions on the design flow factors.